226k views
0 votes
What can you say about the end behavior of the function f(x)=-4x^6+6x^2-52

2 Answers

3 votes

f(x) = -4x^6 +6x^2-52

The leading coefficient is negative so the left end of the graph goes down.

f(x) is an even function so both ends of the graph go in the same direction.

What can you say about the end behavior of the function f(x)=-4x^6+6x^2-52-example-1
User Harry Stevens
by
4.4k points
4 votes

Answer:

As x gets smaller, pointing to negative infinity, the value of f decreses, pointing to negative infinity.

As x gets increases, pointing to positve infinity, the value of f decreses, pointing to negative infinity.

Explanation:

To find the end behaviour of a function f(x), we calculate these following limits:


\lim_(x \to +\infty) f(x)

And


\lim_(x \to -\infty) f(x)

In this question:


f(x) = -4x^(6) + 6x^(2) - 52

At negative infinity:


\lim_(x \to -\infty) f(x) = \lim_(x \to -\infty) -4x^(6) + 6x^(2) - 52

When the variable points to infinity, we only consider the term with the highest exponent. So


\lim_(x \to -\infty) -4x^(6) + 6x^(2) - 52 = \lim_(x \to -\infty) -4x^(6) = -4*(-\infty)^(6) = -(\infty) = -\infty

So as x gets smaller, pointing to negative infinity, the value of f decreses, pointing to negative infinity.

Positive infinity:


\lim_(x \to \infty) f(x) = \lim_(x \to \infty) -4x^(6) + 6x^(2) - 52 = \lim_(x \to \infty) -4x^(6) = -4*(\infty)^(6) = -(\infty) = -\infty

So as x gets increases, pointing to positve infinity, the value of f decreses, pointing to negative infinity.

User Caligoanimus
by
4.2k points